The Think Pair Share Learning Model For Developing Critical Thinking Skills In Mathematics Among Eighth Grade Students - Damanik, Martha Hart; Tambunan, Lois Oinike; Sinaga, Chirsta Voni Rouina (CV Putra Publisher, 2025)
This study aims to determine the effect of the think pair share learning model on the mathematical critical thinking skills of class VIII at UPTD SMP Negeri 7 Pematangsiantar. The sample in this study was class VIII-4, totaling 30 students. The research data was obtained from questionnaires and tests. The questionnaire serves to determine whether students have implemented the think pair share learning model. The test serves to determine students' mathematical critical thinking skills on the material of the system of linear equations in two variables (SPLDV). The test consisted of 5 questions and a questionnaire of 30 items, after going through validity and reliability tests, was declared valid and reliable. The design used in this study was a one-shot case study. The data analysis technique used prerequisite tests, namely the normality test and the linearity test. To test whether the think pair share learning model affects mathematical critical thinking skills, a simple linear regression test was used. Based on the research data, the regression equation Y = 29.354 + 0.828X was obtained. The significance test of the influence was obtained and tcount > ttable (9.642 > 2.048) or p (sig.) < 0.05 (0.000 < 0.05) so that there is a significant influence between the think pair share learning model on the mathematical critical thinking ability of class VIII students at UPTD SMP Negeri 7 Pematangsiantar in the 2025/2026 academic year. The variance contribution of variable X (think pair share learning model) to variable Y (mathematical critical thinking ability) is 76.9%.